Optical characterization of cubic AlGaN/GaN quantum wells - Kohler, U.; As, D. J.; Potthast, S.; Khartchenko, A.; Lischka, K.; Noriega, O. C.; Meneses, E. A.; Tabata, A.; Rodrigues, SCP; Scolfaro, LMR; Sipahi, G. M.; Leite, JR (Wiley-Blackwell, 2002)
Cubic phase group III-nitrides were grown using RF plasma assisted Molecular Beam Epitaxy on GaAs (001) substrates. High-resolution X-ray diffraction, photoluminescence, cathodoluminescence and photoreflectance measurements were employed to characterize the structural and optical properties of GaN/AlxGa1-xN Multi Quantum Well (MQW) structures, in which both Aluminum content and well widths were varied. The observed quantized states are in agreement with first-principles based theoretical calculations.